Let us solve the sysytem:
"\\begin{cases} \\frac{dx}{dt}=-2x+7y \\\\ \n\\frac{dy}{dt}=3x+2y \\end{cases}" "x(0)=9" and "y(0)=-1"
The second eqution is equivalent to "x=\\frac{1}{3}( \\frac{dy}{dt}-2y)", and therefore, "\\frac{dx}{dt}=\\frac{1}{3}( \\frac{d^2y}{dt^2}-2\\frac{dy}{dt})" . Let us put these in the first equation:
"\\frac{1}{3}( \\frac{d^2y}{dt^2}-2 \\frac{dy}{dt})=-2\\cdot\\frac{1}{3}( \\frac{dy}{dt}-2y)+7y"
"\\frac{1}{3} \\frac{d^2y}{dt^2}-\\frac{2}{3} \\frac{dy}{dt}=-\\frac{2}{3}\\frac{dy}{dt}+\\frac{4}{3}y+7y"
"\\frac{1}{3} \\frac{d^2y}{dt^2}=\\frac{25}{3}y"
"\\frac{d^2y}{dt^2}-25y=0"
The characteristic equation "k^2-25=0" of the last differential eqution has the solutions "k=5" and "k=-5." Consequently, its general solution is of the form
"y(t)=C_1e^{5t}+C_2e^{-5t}"
"\\frac{dy}{dt}=5C_1e^{5t}-5C_2e^{-5t}"
Thus, "x=\\frac{1}{3}( \\frac{dy}{dt}-2y)=\\frac{1}{3}( 5C_1e^{5t}-5C_2e^{-5t}-2(C_1e^{5t}+C_2e^{-5t}))=C_1e^{5t}-\\frac{7}{3}C_2e^{-5t}."
If "x(0)=9" and "y(0)=-1", then "9=x(0)=C_1-\\frac{7}{3}C_2" and "-1= y(0)=C_1+C_2" .
It follows that "C_1=2,\\ C_2=-3."
Therefore, the solution is of the form:
"\\begin{cases} x(t)=2e^{5t}+7e^{-5t}\\\\\ny(t)=2e^{5t}-3e^{-5t}\n\\end{cases}"
Comments
Leave a comment